2017
DOI: 10.1080/10495398.2017.1313269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recombinant Human Lactoferrin on Osteoblast Growth and Bone Status in Piglets

Abstract: Lactoferrin (LF), an ~80 kDa iron-binding glycoprotein, modulates many biological effects, including antimicrobial and immunomodulatory activities. Recently, it was shown that LF also regulates bone cell activity, suggesting its therapeutic effect on postmenopausal bone loss. However, a minimal amount is known regarding the effects of recombinant human LF (rhLF) supplementation on bone status in young healthy infants. We found osteoblast cell differentiation was significantly promoted in vitro. Furthermore, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 62 publications
1
10
1
1
Order By: Relevance
“…It is thought to promote osteoblast proliferation and differentiation by interaction with the LRP1 receptor and activation of p42/44 MAPK signalling [64]. In contrast to previous studies [36][37][38], lactoferrin was here found to have no effect on osteogenic differentiation at concentrations of 100 µg/mL and below, whilst 1000 µg/mL significantly reduced the proliferation, ALP activity, and mineralised matrix deposition. Where mineralised nodules did form at 1000 µg/mL, they appeared morphologically normal but were very small.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…It is thought to promote osteoblast proliferation and differentiation by interaction with the LRP1 receptor and activation of p42/44 MAPK signalling [64]. In contrast to previous studies [36][37][38], lactoferrin was here found to have no effect on osteogenic differentiation at concentrations of 100 µg/mL and below, whilst 1000 µg/mL significantly reduced the proliferation, ALP activity, and mineralised matrix deposition. Where mineralised nodules did form at 1000 µg/mL, they appeared morphologically normal but were very small.…”
Section: Discussioncontrasting
confidence: 96%
“…Whilst bovine-derived lactoferrin was used in this study with human-origin cells, it has previously been shown that bovine, human, and recombinant forms have comparable effects; therefore, this is unlikely to be the reason for not detecting any anabolic effect [36]. Previous reports of an increasing ALP activity in response to lactoferrin have shown an immediate increase after only 24 hours of exposure in normal human osteoblasts, MC3T3-E1, and primary murine osteoblasts [38,65], but the effects were not examined at later time points. A continuous exposure for 35 days at concentrations of up to 1000 µg/mL showed a dose-dependent increase in mineralisation in the two murine cell types [65], although minimal mineralisation was observed in the absence of lactoferrin despite the use of 10 mM βGP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of Recombinant human Lf (rhLf) to the culture media of NHOst human osteoblast cells resulted in increased level of alkaline phosphatase (ALP), a marker for osteogenic activity, and enhanced ERK1/2 activation, which is a part of proliferative signaling. Treatment of piglet with rhLf has increased the serum calcium and bone mineral density compared to control piglets [ 217 ].…”
Section: Pharmaceutical Applicationsmentioning
confidence: 99%
“…9 Outra pesquisa realizada, buscou mensurar o aumento da densidade mineral óssea em crianças, mostrando um aumento de 5% em todo o corpo, dimi-nuindo em aproximadamente 9% as chances de ocorrer fratura na infância. 10 Desse modo, observa-se que whey protein tem diversos benefícios para o corpo humano, além da sua ação no tecido ósseo, apresenta também aumento no nível do antioxidante glutationa,ajuda na prevenção de cânceres, possui atividade antibacteriana e aumento da imunidade passiva. 6…”
Section: Interação Do Whey Benefíciounclassified